Penelitian Pertashop & BBM Satu Harga Terhadap Reputasi PERTAMINA Diukur Dengan Ekuitas Merek Berbasis Pelanggan - Elang Rimba Dewata; Farida Hariyati; Shahrina Md Nordin (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
Reputation is not only about corporate management, product, and their value. But it also includes the process of how to get a good reputation from the stakeholder perception. One of the ways is through Corporate Social Responsibility (CSR) Programs. This research objective tries to find and explain the significant effect of the public’s perception about CSR programs by Pertamina on corporate reputation measured by Customer-Based Brand Equity (CBBE). This research uses a quantitative approach with survey methods. The theory that underlies this research is stakeholder theory with the concept of Customer-Based brand equity. The result of this research shows the significant effect of local communities’ perception about corporate image and CSR programs is very high (99,40%) on local communities CBBE as the measurement of corporate reputation. These results indicate that the CSR program plays a vital role in determining the company's reputation in the local community's perception. Improving the CSR programs, CSR personnel, CSR executives are very affecting the corporate image and building a better CBBE and corporate reputation.